Implementation of Anti-Corruption Education in Building Student Character At SMP Negeri 1 Kabil - Sri Wahyuni; Sastro Mustapa Wantu; Sukarman Kamuli (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to describe the implementation of anti-corruption education in building student character at SMP Negeri 1 Kabila. Anti-corruption education is an important part of developing students' character with integrity, honesty, and responsibility. In its implementation, this education is integrated through various methods, such as classroom learning, daily behavioral habits, and teacher role models. The core values instilled include honesty, independence, and responsibility. This study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation with teachers, principals, and students. The results showed that the implementation of anti-corruption education in this school had a positive influence on changing students' attitudes and behavior, particularly in increasing their moral awareness and ethical behavior. However, its implementation still faces several obstacles, including limited resources, resistance to change from some teachers and students, and a school culture that does not fully support anti-corruption values. Therefore, support from all school elements is essential to optimize the role of anti-corruption education in developing students' character with resilience and integrity. The conclusion of this study indicates that although anti-corruption education has begun to be implemented and has had a positive impact on student behavior, its success still depends on comprehensive support from the school, teachers, and the surrounding community. Increased resources and strengthening of a school culture that supports anti-corruption values are needed for optimal implementation of this education.